Geometric morphometrics analysis of wing venation for identification of selected forensically important flies in Malaysia / Nur Ayuni Dayana Mohd Puaad - Nur Ayuni Dayana , Mohd Puaad (2021)
Entomological evidence has become one of the elements in assisting the criminal investigation. The presence of various insects at the crime scene or on the dead body often giving clues on the manner of death particularly in suicide and homicide cases. Flies for instance, are the most common and apparent insect at the murder scene and frequently, a specific fly species would be present at the specific location and time. From here, the estimation of post mortem interval will be made upon various criteria; the time of death or the synchronisation between the locations of the murder and the location of the body was found. Thus, it is very crucial to acquire the speciation information of the fly as fast as we could to help the investigation processes. Hence, an effective, economical and rapid method is needed for the identification of these insects. This study was focused on using quantitative methods for species identification of the flies through geometric morphometrics analysis. The analysis on the wings of the flies was conducted by measuring the venation via landmark method. Fifteen forensically important fly species in Malaysia from the Calliphoridae and Sarcophagidae families were chosen from an archived collection as the subject of this analysis. The measurement obtained from the geometric morphometrics analysis in the form of thinplate- spline data were subjected to the Generalised Procrustes Analysis (GPA), Principal Component Analysis (PCA) and Heat Map Analysis. From PCA, the differences between both families and the distribution of fly species within Calliphoridae family were quite obvious compared to Sarcophagidae family. Geometric morphometrics analysis were also carried out on 36 crime scene sample, and 14 randomly chosen crime scene samples were sent for DNA sequence analysis for verification. From this study, geometric morphometrics method was shown to have the potential to become a useful identification and diagnostic tools for forensically important fly species in Malaysia.